Ultrafast Nonlinear Optical Response in GaN/AlN Quantum Dots for Optical Switching Applications at 1.55 μm - Valdueza-Felip, S.; Naranjo, F. B.; González-Herráez, M.; Monroy, E.; Solís, J. (IntechOpen, 2012)
None